(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role of modern geodetic instruments and their applications in the process of biodiversity inventory. It is very important to have accurate and reliable data for biodiversity conservation and species monitoring. The article discusses the advantages of GPS systems, GIS (Geographic Information Systems), laser scanners, drones and other geodetic technologies in studying biodiversity, their role in identifying species and analyzing their habitats. The possibilities of obtaining accurate information about the location and ecological conditions of species using geodetic instruments, as well as quickly detecting ecological changes are considered. These instruments and technologies are widely used not only in scientific research, but also in the formulation of environmental policies and natural resource management. The article provides detailed information on the importance of geodetic instruments in biota inventory, their role in environmental protection and sustainable development, as well as prospects for studying biodiversity using new technologies in the future.